Variation of Number of Pores on the Carapaces of Group A Species of the Genus Loxoconcha (Crustacea, Ostracoda) Following the Molting - Le, D. D. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2023)
Phylogeny of all extant twenty-eight species of Group A of the genus Loxoconcha are examined in this study. Basing on the total number of pores on carapaces, three species subgroups of this genus are shown by Differentiation of Distributional pattern of Pore-system (DDP) analysis. All species possess identical number and same distributional pattern of pore-system in and before A-4 instar. The difference in the total number of pores on carapaces is found from the instar A-3 to adult and thus three patterns are recognized. In the instar A-3, these numbers of subgroup A1, A2 and A3 are 42, 43 and 44, respectively. Additionally, the present study shows an identical number of anterior false radial pores among the subgroups at all instars. However, the number of posterior false radial pores is different among three subgroups from A-3 instar. In this instar, these numbers of subgroup A1, A2 and A3 are equivalent to 3, 4 and 5. By combination of this study and previous studies, geographical distribution of three subgroups is shown. Species of subgroup A1 distribute worldwide except the distributional areas of subgroups A2 and A3. While, species of subgroup A2 and A3 only reside in Atlantic coasts of Europe, northern Africa and coasts of the Mediterranean Sea.